Stakeholder Based Framework for M&A Management - ВашакмадзеТеймураз Теймуразович; МартиросянЭмиль Георгиевич; СергееваАнастасия Александровна (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2013)
<span data-sheets-value=""1":2,"2":"Теймураз Теймуразович Вашакмадзе НИУ ВШЭ "" data-sheets-userformat=""2":8403715,"3":[null,0],"4":[null,2,14540253],"11":0,"12":0,"14":[null,2,-704643072],"15":""Noto Sans", -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, Oxygen-Sans, Ubuntu, Cantarell, "Helvetica Neue", sans-serif","16":11,"26":400">Authors: Teimuraz Teimurazovich Vashakmadze - National Research University "Higher School of Economics." Emil G. Martirosyan Anastasia Alexandrovna Sergeeva Strategic development and value of the company is strongly influenced by different groups of stakeholders. Considering the growing M&A activity, there is a high need for a stakeholder based management system and metrics which traces the interests of all stakeholders that can be used by practitioners. This paper develops a conceptual framework of the stakeholder management system for M&A deals, called the SUN Cube (Martirosyan and Vashakmadze, 2013) and shows how the SUN Cube framework can be used in capturing synergies during the post-merger integration process.